Heterozygous truncating variant of TAOK1 in a boy with periventricular nodular heterotopia: a case report and literature review of TAOK1-related neurodevelopmental disorders - Anna Cavalli; Stefano Giuseppe Caraffi; Susanna Rizzi; Gabriele Trimarchi; Manuela Napoli; Daniele Frattini; Carlotta Spagnoli; Livia Garavelli; Carlo Fusco (BMC, 2024)
Abstract Background Thousand and one amino-acid kinase 1 (TAOK1) encodes the MAP3K protein kinase TAO1, which has recently been displayed to be essential for neuronal maturation and cortical differentiation during early brain development. Heterozygous variants in TAOK1 have been reported in children with neurodevelopmental disorders, with or without macrocephaly, hypotonia and mild dysmorphic traits. Literature reports lack evidence of neuronal migration disorders in TAOK1 patients, although studies in animal models suggest this possibility. Case presentation We provide a clinical description of a child with a neurodevelopmental disorder due to a novel TAOK1 truncating variant, whose brain magnetic resonance imaging displays periventricular nodular heterotopia. Conclusions To our knowledge, this is the first report of a neuronal migration disorder in a patient with a TAOK1-related neurodevelopmental disorder, thus supporting the hypothesized pathogenic mechanisms of TAOK1 defects.